2016
DOI: 10.1097/md.0000000000002462
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Nongenitourinary Cancers in Patients With Spinal Cord Injury

Abstract: Little information is available regarding the risk of nongenitourinary (GU) cancers in patients with spinal cord injury (SCI). The authors conducted a nationwide population-based study to investigate whether a higher risk of non-GU cancer is seen among patients with SCI.Data retrieved from the National Health Insurance Research Database of Taiwan were used in this study. A total of 41,900 patients diagnosed with SCI between 2000 and 2011 were identified from the National Health Insurance Research Database and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
0
12
0
3
Order By: Relevance
“…A greater risk of hematologic and esophageal cancer has been reported in patients with SCI [2], but the mechanisms underlying these associations are not established. A former study has shown that miR-125a-5p have a reduced expression in patients with esophageal squamous cell carcinoma [18] suggesting that this miRNA can function as a tumor suppressor in this type of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A greater risk of hematologic and esophageal cancer has been reported in patients with SCI [2], but the mechanisms underlying these associations are not established. A former study has shown that miR-125a-5p have a reduced expression in patients with esophageal squamous cell carcinoma [18] suggesting that this miRNA can function as a tumor suppressor in this type of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…According to the 2014 National SCI Statistical Center (NSCISC) annual report [1], neoplasms are the third leading cause of death in SCI individuals in the United States. Patients with SCI have an increased risk of developing esophageal, bladder and hematologic malignancies, such as multiple myeloma chronic or acute myeloid leukemia, and lymphoma, compared with normal population [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of these genes is associated with tumorigenesis by increasing chromosomal instability. Activation of the cell cycle pathway after SCI and subsequent cell proliferation is associated with a wide range of damage caused by secondary mechanisms after SCI and may also be associated with a higher risk of cancer in patients with SCI [26].…”
Section: Discussionmentioning
confidence: 99%
“…11,59,63 Although it is unknown if NASH occurs at a higher frequency after SCI, hepatitis, cirrhosis, and hepatic carcinoma do have a significantly higher frequency in SCI individuals than in the general population. 64,65 Green tea and its catechins protect against inducible NAFLD by decreasing oxidative stress, inflammatory responses, plasma aminotransferases, triglycerides, and lipoproteins. 30,31,43,44 The close relationship of these factors to the development of NAFLD supported the hypothesis that dietary green tea would also protect against NAFLD-like liver pathology in chronic SCI; however, this was not observed.…”
Section: Discussionmentioning
confidence: 99%